2016
DOI: 10.5897/err2015.2616
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relation between metacognitive understanding of what is listened to and metacognitive awareness levels of secondary school students

Abstract: The purpose of the study is to reveal the relation between the Metacognitive Understanding of What is Listened and the Metacognitive Awareness Levels of Secondary School Students. 210 students, who were at 5, 6, 7, and 8th Grades studying at Turgut Ozal Secondary School in Bulanik County of the city of Mus, participated in the study. The Metacognitive Understanding of What is Listened Awareness Scale, which was developed by Katrancı and the Metacognitive Awareness Scale, which was developed by Sperling whose v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…In the same vein, Chantharanuwong, et al, (2012), describe that male and female teachers do not have any difference in their metacognitive abilities. In contrast, previous research also revealed that female teachers have better metacognitive abilities than male teachers (Akin, 2016;Ciascai & Lavinia, 2011). Moreover, the results of this study indicate that teachers have significant differences in classroom learning environment on the base of various factors such as gender, discipline and teaching level.…”
Section: Discussioncontrasting
confidence: 91%
“…In the same vein, Chantharanuwong, et al, (2012), describe that male and female teachers do not have any difference in their metacognitive abilities. In contrast, previous research also revealed that female teachers have better metacognitive abilities than male teachers (Akin, 2016;Ciascai & Lavinia, 2011). Moreover, the results of this study indicate that teachers have significant differences in classroom learning environment on the base of various factors such as gender, discipline and teaching level.…”
Section: Discussioncontrasting
confidence: 91%
“…The findings show that there are no significant differences between men and women (Garzón et al, 2020). Other data also provides information that women have better metacognitive skills than men (Erhan, 2016). On the other hand, there is research that concludes that there are no differences in metacognitive activity between men and women (Demirel et al, 2015).…”
Section: Description Of Students' Metacognitive Skills Using Planning...mentioning
confidence: 87%
“…Such correlations have been observed across various sociodemographic groups, except for young men. This may be explained by general overconfidence, among young males, when judging their performance 63,64 , as well as females showing better metacognition than men 65 . The moderate correlation may arise by the fact that it has been shown that adults with typical face recognition abilities have only modest insight into their ability to recognize faces on behavioral tests 66,67 .…”
Section: Insights Into Face Recognitionmentioning
confidence: 99%